Comparison of Business Income on Tajuk and Manjung Short Onion Farming in Tande Village Majene Regency West Sulawesi - Ahmad Fausi; Deddy Ibrahim Rauf (PT. Maju Malaqbi Makkarana, 2023)
Red onion is a vegetable commodity that has high economic value in terms of fulfilling national consumption and sources of income. There are 2 types of shallots planted by farmers in the Tande Village, namely Tajuk and Manjung. There fore we want to see which variety is more profitable. This study aims: (1) to compare the productivity of Tajuk and Manjung shallot farming in Tande Village, East Banggae District, East Banggae Regency (2) to determine the comparison of Tajuk and Manjung shallot farming income in Tande Village, East Banggae District, East Banggae Regency. The research method used is by means of purposive sampling by way of consideration that is having a lot of farmer groups. The samples in this study were 20 farmers of the Tajuk variety and 20 samples of the Manjung variety of shallot farmers. The results showed that (1) the average shallot productivity for the Tajuk variety (Sipatuo Farmers Group) on a 3.40 ha land area was 3.42 tons/ha with an average production of 11.53 tons, and on a 1 ha land area the average the average productivity is 8.50 tons/ha with a total production of 8.50 tons. Whereas for the Manjung variety (Lestari Green Farming Group) the average productivity on a land area of 3.25 Ha is 3.18 Tons/Ha with a total production of 10.32 Tons, - the average shallot productivity on 1 Ha land is 7.90 Tons /Ha with total production of 7.90 tons. (2) the average income of Tajuk shallot farmers is greater than the average income of Manjung shallot farmers. The average income of shallot crowns on a land area of 3.40 Ha is Rp. 79,694,286 the average income of farmers on 1 Ha of land is Rp. 132,486,668. Whereas for the Manjung variety, the average income on a land area of 3.25 is Rp. 63,679,020, - the average income of farmers on 1 Ha of land is Rp. 120,517,501.